2011
DOI: 10.1021/bi1018144
|View full text |Cite
|
Sign up to set email alerts
|

Binding between a Distal C-Terminus Fragment of Cannabinoid Receptor 1 and Arrestin-2

Abstract: Internalization of G-protein coupled receptors is mediated by phosphorylation of the C-terminus, followed by binding with the cytosolic protein arrestin. To explore structural factors that may play a role in internalization of cannabinoid receptor 1 (CB1), we utilize a phosphorylated peptide derived from the distal C-terminus of CB1 (CB15P454-473). Complexes formed between the peptide and human arrestin-2 (wt-arr21-418) were compared to those formed with a truncated arrestin-2 mutant (tr-arr21-382) using isoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 73 publications
0
27
0
Order By: Relevance
“…As described in the introduction, the binding between β-arr2 and CB 1 R as well as a role for β-arrestins in the desensitization of CB 1 R have been demonstrated by former studies (Bakshi et al, 2007;Daigle et al, 2008aDaigle et al, , 2008bJin et al, 1999;Kouznetsova et al, 2002;Nguyen et al, 2012;Singh et al, 2011). Therefore, the role of β-arr2 in CB 1 R endocytosis may seem to be a logical consequence of its recruitment to the receptor.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…As described in the introduction, the binding between β-arr2 and CB 1 R as well as a role for β-arrestins in the desensitization of CB 1 R have been demonstrated by former studies (Bakshi et al, 2007;Daigle et al, 2008aDaigle et al, , 2008bJin et al, 1999;Kouznetsova et al, 2002;Nguyen et al, 2012;Singh et al, 2011). Therefore, the role of β-arr2 in CB 1 R endocytosis may seem to be a logical consequence of its recruitment to the receptor.…”
Section: Discussionmentioning
confidence: 82%
“…It has been demonstrated that serine and threonine residues at the C-terminus of CB 1 R are involved in its β-arr2 binding and agonist-induced endocytosis (Daigle et al, 2008b;Hsieh et al, 1999). In contrast to the various studies that clearly point to an interaction between CB 1 R and β-arr2 upon agonist stimulation, no direct data have been hitherto presented concerning the β-arr1 binding of CB 1 R. In some structural studies, the association of β-arr1 with a synthesized CB 1 R C-terminus has been shown (Bakshi et al, 2007;Singh et al, 2011), however, such binding has not been demonstrated with the intact CB 1 R in living cells.…”
mentioning
confidence: 99%
“…For example, probable G-protein-coupled receptor kinase phosphorylation sites have been identified Jin et al, 1999;Daigle et al, 2008) and isolated fragments of the CB 1 R C-terminus can bind to b-arrestins (Singh et al, 2011;Bakshi et al, 2007) and GASP1 (Martini et al, 2007). Prolonged agonist exposure downregulates CB 1 Rs expressed in HEK-293 (Shapira et al, 2003) but not N18TG2 cells (McIntosh et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…We also sampled side‐chain conformation of the CB1 Ct peptide using the rotamer database and obtained the best combination of side‐chain angles by Monte Carlo simulated annealing. Among the highest scored ROSETTA‐predicted models, we selected five models that agreed with NMR data …”
Section: Methodsmentioning
confidence: 99%
“…Although these NMR studies provided invaluable insight into the CB1 Ct peptide structure, it is necessary to determine the structure of CB1 Ct in contact with the G protein to gain structural information about the potential role of CB1 Ct in G protein signaling. In this study, we elucidated the plausible interactions of CB1 Ct with the G protein by building on our prior modeling effort of the CB1‐Gi complex lacking CB1 Ct (CB1( no Ct )‐Gi) .…”
Section: Introductionmentioning
confidence: 99%